Evidências à intervenção de enfermagem controle de infecção da classificação das intervenções de enfermagem: orientação e ensino sobre a lavagem das mãos - Brito, Lilian Salgado Cunha [UNESP] (2015)
Introduction: The right hand hygiene is a simple and effective way to helping to control infection. The teaching of hand washing to the healthcare team, patients and visitors are activities assigned to the nurse, described in the intervention Infection Control on the Nursing Interventions Classification (NIC).With the movement of evidence-based nursing and the advancement of information systems, the conscious, explicit and judicious use of the best available evidence in clinical practice has become a responsibility of nurses to provide care. This study aims to evaluate the level of evidence of three nursing activities of the infection control intervention.Objective: To evaluate the level of evidence of nursing activities related to the guidance and education on hand washing, the Infection Control nursing intervention, presented in the Nursing Interventions Classification (NIC).Method: Integrative review of the literature study. The study is based on three research questions about the level of evidence hands wash education for health professionals, patients and visitors. Three search strategies were used in the Cochrane databases, CINAHL and PubMed in January / 2015 and included articles published in English, Portuguese or Spanish from 2004 to 2015. We used the level of evidence classification of Joanna Briggs Institute.Results: In teaching the healthcare professional, we included 39 articles and studies presented evidence level 1 (01; 2%), 2 (11; 28%) and 3 (27; 69%). In teaching the patient five articles were included, who had evidence level 1 (01; 20%), 2 (01; 20%) and 3 (03; 60%). In teaching the visitor were included five articles, all presented evidence level 2 (05; 100%). Based on the results, was built a video about the teaching of hands washing for use in hospital environments, with focus on the patient and visitors.Conclusion: The nursing activities related to the teaching of hand washing ...